OBTAINING RECOMBINANT EXTRACELLULAR FRAGMENTS OF GPR161 RECEPTOR - Kanaev , D.B.; Mukanov, K.K.; Adish , Zh.; Tokhtarova , L.; Zhumabekova , S.; Inirbay , B.; Tursunov , K.A.; Ramankulov , Ye.M.; Mukantayev , K.N. (Eurasian Journal of Applied Biotechnology, 2019)
The GPR161 is a receptor of the GPCR family and identified as a prognostic biomarker for triple negative breast cancer (TNBC). TNBC characterized by lack of expression of the estrogen receptor (ER), progesterone receptor (PR) and epidermal growth factor receptor (Her2), early recurrence and poor prognosis. The GPR161 is an important regulator of the proliferation and migration of cancer cells. However, anti-GPCR receptor drugs are rarely used in the treatment of cancer, despite evidence of receptor involvement in various aspects of cancer development. Upon receipt of monoclonal antibodies, the success of the study is associated with the presence in sufficient quantities of pure antigen preparations. Recently, gene synthesis under de novo conditions has become a powerful tool in biotechnology. A number of methods have been described, representing thermodynamic balanced methods based on polymerase chain reaction (PCR). This paper presents the results of gene synthesis and the preparation of a recombinant extracellular fragment of the receptor. To obtain a recombinant protein, an area located outside the cell membrane between the 4th and 5th helix of the receptor was selected. A genetic construct based on the pET32 vector carrying the extracellular fragment of the human GPR161 receptor has been developed and obtained. Strain Escherichia coli BL21/pET32/TM4-5GPR161 producing recombinant extracellular fragment rTM4-5 GPR161 was obtained. The conditions for the isolation and purification of recombinant protein were determined, and its immunogenic properties were studied. Purified recombinant protein TM4-5GPR161 in its immunological characteristics suitable for the production of strains of hybrid cells producing monoclonal antibodies to the GPR161 receptor.